Centre-based supervised child-parent contact in Ireland: The views and experiences of fathers, supervisors and key stakeholders. (May 2019) - Kiely, Elizabeth; O' Sullivan, Nicola; Tobin, Mary
Abstract: The paper presents findings from a study of centre-based supervised child-parent contact. The purpose of the research was twofold: to ascertain the views and experiences of birth fathers on all aspects of the supervised child-parent contact they experienced in a centre; and to find out from centre supervisors their views of engaging fathers and supervising contact, and from key stakeholders and referral agents (a community project worker, a child protection social worker, Guardians ad Litem and a family law solicitor) their perceptions of the supervised contact provision in the centre. Interviews with five fathers having supervised child-parent contact and three focus group discussions with seven staff members and six stakeholders were undertaken. While the study is exploratory, the findings show that gender is a feature meriting consideration in the supervised child parent contact setting; and that child-centred values, family-centred values and the demands of operating the centre are held in tension so that the purpose and scope of supervised contact can be interpreted and experienced differently. While optimal supervised child -parent contact is generally perceived as a short-term arrangement, there was some evidence of long-term service use, which was a significant issue for the fathers concerned. The fathers valued relationship-based supervision practice to a greater extent than the supervisor and stakeholder participants, who put greater emphasis on skills required for supervision. Fathers expressed concerns about what they or their children can say or do during contact visits in view of how it may be observed, interpreted and reported. The findings suggest the need for a gender-sensitive approach in supervision practice; the value of a common framework for assessing what is observed in contact visits; and the intensification of strategies to facilitate and to recognise progress and the prioritisation of short term supervised contact arrangements with the required supports. Highlights: A qualitative study of centre-based supervised child-parent contact. Gender features in supervised child-parent contact in diverse ways. The purpose and scope of supervised child-parent contact can be interpreted and experienced differently. Responsive short-term supervised child-parent contact with key supports is important for families.